Construction of foam-templated Antarctic krill oil oleogel based on pea protein fibril and ι-carrageenan. - Sun, Chang; Wei, Zihao; Xue, Changhu (Carbohydrate Polymers, 2025)
Edible plant-based oleogels with zero trans-fat are promising solid fat substitutes. In this study, Antarctic krill oil (AKO) oleogels prepared from pea protein fibril (PPF) and ι-carrageenan (CG) by foam-templated method were developed for the first time. The modulation of the ratio of PPF and CG concentration on the structure and properties of foam, cryogel and oleogel was investigated and the potential formation mechanism of the foam-templated oleogel was explained. The results demonstrated that the addition of CG significantly decreased the foam size and enhanced the foam stability. The oil absorption and oil holding ability of the dense and reticular porous structure of the cryogel was demonstrated. Fourier infrared spectroscopy confirmed the interaction between PPF and CG involved in the formation of cryogels. With the addition of CG, the network structure and mechanical strength of the cryogel were reinforced, leading to more compact pores and higher capillary suction, which was appropriate for the establishment of good viscoelastic semi-solid oleogels. In addition, the oleogel was effective in masking the fishy odor of AKO. The significance of this study lies in its provision of a novel approach to the preparation of the foam-templated oleogel with PPF and CG as the oleogelators.